Genetic improvement of Saccharomyces cerevisiae for xylose fermentation - Chu, Byron C.H.; Lee, Hung (Biotechnology advances, 2007)
There is considerable interest in recent years in the bioconversion of forestry and agricultural residues into ethanol and value-added chemicals. High ethanol yields from lignocellulosic residues are dependent on efficient use of all the available sugars including glucose and xylose. The well-known fermentative yeast Saccharomyces cerevisiae is the preferred microorganism for ethanol production, but unfortunately, this yeast is unable to ferment xylose. Over the last 15 years, this yeast has been the subject of various research efforts aimed at improving its ability to utilize xylose and ferment it to ethanol. This review examines the research on S. cerevisiae strains that have been genetically modified or adapted to ferment xylose to ethanol. The current state of these efforts and areas where further research is required are identified and discussed.